POLITISI SENIOR DI DPRD KOTA PEKANBARU TAHUN 2014–2019 - Boby Rizky Ananda; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In the context of agenda indonesia unresolved is he also resistance to the mushrooming in every state institution.The axis of the powers of the state still tersentralistik against he also. isOne example is in kontestasi leadership elections in indonesia that he also plays an important role in the system of rule is informed and versed in mengelolah axis, existing powers while a young person is considered as objects of a system that function and role gerontokrasi kaula young gerontokrasi. have stalled in the systemWe just look back now in general political parties in indonesia were controlled by politisi-politisi old. With the gerontokrasi in a political party this is an embryo that breeds kepartaian oligarchy , the system of rule produced by a handful of party elite party that is small .Not only in the political gerontokrasi arrived but also the economic and cultural system .Problems related to research is as follows: what formation he also in the council pekanbaru 2014-2019 years .Aimed at described and knows he also formations in the council pekanbaru 2014-2019 years . Research approach used in this research is a qualitative approach.In this study researchers used. interviewThe research results it produces the conclusion that senior politicians in the council pekanbaru also have an influence on government, in pekanbaru so they can be said as senior politician who can influence policy in the government pekanbaru  Key Words: Senior Politician , Gerontokrasi